2021
DOI: 10.3390/educsci11100620
|View full text |Cite
|
Sign up to set email alerts
|

Controlling-Supportive Homework Help Partially Explains the Relation between Parents’ Math Anxiety and Children’s Math Achievement

Abstract: Previous research has shown that math homework help of higher-math-anxious parents impedes children’s math learning and facilitates the development of math anxiety. In the present study, we explored a possible explanation for this phenomenon by examining the relations between parents’ math anxiety, their math homework-helping styles (i.e., autonomy- and controlling-supportive), and their child’s math achievement. Parents of children ages 11 to 14 completed an online survey. Using path analysis, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 84 publications
1
18
2
Order By: Relevance
“…Another approach could be to explore whether the age of the child and the difficulty of the mathematics concepts matter for the relations between parents math anxiety and children's later mathematics performance. Although in our study we found no association between parents math anxiety and children's achievement, a more recent study using concurrent data with older children, Retanal et al 49 found that parents' math anxiety negatively predicted children's mathematics achievement (M age = 6.80 years). It would be worth exploring if this association is driven by anxiety experienced when parents engage themselves in mathematics or by anxiety experienced when parents engage with their older child in mathematics.…”
Section: Parents' Math Anxiety and Children's Numeracy Skillscontrasting
confidence: 99%
“…Another approach could be to explore whether the age of the child and the difficulty of the mathematics concepts matter for the relations between parents math anxiety and children's later mathematics performance. Although in our study we found no association between parents math anxiety and children's achievement, a more recent study using concurrent data with older children, Retanal et al 49 found that parents' math anxiety negatively predicted children's mathematics achievement (M age = 6.80 years). It would be worth exploring if this association is driven by anxiety experienced when parents engage themselves in mathematics or by anxiety experienced when parents engage with their older child in mathematics.…”
Section: Parents' Math Anxiety and Children's Numeracy Skillscontrasting
confidence: 99%
“…Thus, parents’ math anxiety and involvement may mutually reinforce one another, creating an unconstructive cycle. Consistent with the idea that parents’ math anxiety and control co-occur, math-anxious parents report using more control and less autonomy support when helping children with math homework (Retanal et al, 2021).…”
Section: The Role Of Parents’ Math Anxiety In Controlling and Autonom...mentioning
confidence: 86%
“…Given that math-anxious adults avoid math (e.g., Hembree, 1990; Krinzinger et al, 2009), math-anxious parents may also be controlling to ensure children finish quickly; autonomy-supportive strategies may be more time intensive as they involve allowing children to try out their own strategies, many of which may not work. In addition, math-anxious parents may be inflexible such that they insist children use their strategies even when they are inconsistent with what children are learning at school (Maloney et al, 2015; Retanal et al, 2021). The controlling (vs. autonomy-supportive) nature of math-anxious parents’ involvement may amplify their math anxiety as it may backfire (see below), leading parents to feel even more incapable when it comes to math.…”
Section: The Role Of Parents’ Math Anxiety In Controlling and Autonom...mentioning
confidence: 99%
“…Students are less responsive when asked to do assignments. The tasks given by the teacher are only partially done by students independently; the rest is the result of parents' work (Retanal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%